Strategies for an exploratory research structured in university extension project portfolios - Campos , Carla; Gillieron , Elenice Correa (Seven Editora, 2023)
The study was relevant to establish scientific methodological parameters for conducting the Retrospective Exploratory Research (PEx) (2000-2020). PEx sought portfolios of extension projects and their possible types so that the references found could assist in the creation of a portfolio for the university extension project Museu 3D. A tree of keywords with multicriteria connectors and filters was elaborated as structural procedures, according to each search tool. The results, represented by the Venn-Euler diagrams, showed that although the portfolio is widely used in several areas and has an expressive bibliography, references with portfolios related to extension projects are scarce (only seven). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-046